Absorção, acúmulo e exportação de macronutrientes no milho doce cultivado em condições de campo - Borin, Ana Luiza Dias Coelho (2010)
Sweet Corn is a vegetable addressed to industrial processing not widely consumed in natura in Brazil, possibly due to the restricted number of varieties adapted to the Brazilian tropical climate. Studies on the most appropriate management practices, which include the dynamics of nutrient absorption by the culture, are still nonexistent. Thus, the objective of this work was to determine the absorption, accumulation and export of nutrients in sweet corn under field conditions. Simple tropical hybrid was used, on an entirely randomized design comprised of nine treatments (9, 18, 27, 36, 45, 54, 63, 72 and 81 days after emergence) with four replicates. The plants were sampled in every treatment and cut to the soil surface for shoot (plant and ear) evaluation. Both parts were used to determine the absorption of nutrients by the plant and their transmigration to the ear. Daily nutrient absorption rates, as well as the accumulation percentages of nitrogen, phosphorus, potassium, calcium, magnesium and sulfur were evaluated. The pattern of macronutrient accumulation followed the dry matter accumulation of the plants. The decreasing order of macronutrient accumulation at the shoot was: K > N > Mg > P > Ca > S. Most nutrients had a maximum absorption interval around 18 to 27 days after emergence.